Professional BizTalk server 2006 - Jefford, Darren, 1978- (Wrox professional guides., 2007)
This book provides insight into how industry experts have successfully architected, developed, and maintained Microsoft BizTalk Server in mission-critical environments. Authored by highly-regarded consultants with a wealth of knowledge on designing, building, and operating enterprise applications using BizTalk, this comprehensive guide gives you the techniques and best practices you8217;ll need to develop effective projects. Darren Jefford is a Principal Consultant with the Microsoft UK Application Development Consulting (ADC) team who has extensive real-world experience with BizTalk Server and the broader Microsoft platform. Kevin B. Smith formerly worked as a Technical Lead Software Design Engineer for the BizTalk Server Product Team and helped ship three versions of BizTalk Server. Ewan Fairweather works as a Premier Field Engineer for Microsoft, providing onsite support to enterprise customers, including maintaining and optimizing their BizTalk Server solutions. Achitects, developers, testers, and administrators will achieve instant success when they apply the deep technical information covered in this book. They will better appreciate the internal workings of BizTalk Server and will understand detailed solutions for challenges often experienced with BizTalk-based systems.